Currently influential models and approaches in reading comprehension - Sandoval-Cruz, Rosa Isela (Cinzontle, 2018)
Reading comprehension is a national problem in Mexico (Díaz Gutiérrez et al., 2007) and specifically for UJAT students reading in English as a Foreign Language (Perales Escudero, 2011). In order to contribute to a greater understanding of this problem, this paper reviews some influential theoretical models of comprehension: the Psycholinguistic Guessing Game (PGG), the Interactive Compensatory Model, and the Construction-Integration (C-I) model.